2020
DOI: 10.1097/jd9.0000000000000086
|View full text |Cite
|
Sign up to set email alerts
|

Atherogenic Diet Accelerates Ectopic Mineralization in a Mouse Model of Pseudoxanthoma Elasticum

Abstract: Objective: Pseudoxanthoma elasticum (PXE) is a multisystem heritable disorder caused by mutations in the Abcc6 gene. The disease is characterized by ectopic mineralization of the skin, eyes, and arterial blood vessels. Previous studies have suggested that cardiovascular complications in patients with PXE are caused in part by premature atherosclerosis. The aim of this study is to determine the effect of an atherogenic diet on ectopic mineralization. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Early studies suggested that cholesterol-lowering drugs, such as atorvastatin, was able to ameliorate the extent of ectopic mineralization in the Abcc6 −/− mouse model [ 31 ]. In contrast, an atherogenic diet induced hypercholesterolemia and steatosis accompanied by increased mineralization in the soft connective tissues in the same mouse model [ 69 ]. These findings have clinical relevance for the management of PXE in humans.…”
Section: Therapy Development For Ectopic Mineralization Disordersmentioning
confidence: 99%
“…Early studies suggested that cholesterol-lowering drugs, such as atorvastatin, was able to ameliorate the extent of ectopic mineralization in the Abcc6 −/− mouse model [ 31 ]. In contrast, an atherogenic diet induced hypercholesterolemia and steatosis accompanied by increased mineralization in the soft connective tissues in the same mouse model [ 69 ]. These findings have clinical relevance for the management of PXE in humans.…”
Section: Therapy Development For Ectopic Mineralization Disordersmentioning
confidence: 99%